An Uncommon Presentation of Myasthenia Gravis with Thymoma - A Case Report and Review of Literature (Journal of Medicine, 2012)
Myasthenia Gravis (MG) is a rare disease of neuromuscular junction which typically presents with fatigable weakness of cranial and limb muscles. But patient may present with vague symptoms which may mislead physicians to an incorrect diagnosis. We are reporting a 45 year old cobbler presented with the complaints of lack of energy, aching pain in shoulder, back, upper arm and difficulty in swallowing of both solid and liquid food without any diurnal variation for two and half years. He was ultimately diagnosed as a case of MG and thymectomy revealed thymoma. DOI: http://dx.doi.org/10.3329/jom.v13i1.10087 JOM 2012; 13(1): 109-114